Sunflower Based Rations for Small-Medium Milk Producing Dairy Cows - Chimonyo, M.; Ngongoni, N.T.; Mapiye, C.; Mwale, M.; Mupeta, B. (Pakistan Journal of Nutrition, 2009)
Two dairy concentrates (ram press sunflower and sunflower heads) were formulated locally and their effects on the performance of crossbred dairy cows were compared with that of a commercial dairy concentrate. There were no significant differences in body condition and milk production responses by crossbred dairy cows to sunflower based diets compared to commercial dairy concentrates (p > 0.05). It was suggested that the sunflower based rations can be used as cheaper alternatives to conventional dairy concentrates. The ram press sunflower cake, in particular is an option that may be used by smallholder dairy farmers to formulate local dairy concentrate, which influence dairying to a similar extent as the commercial dairy concentrate but cheaply. More research is required to determine fermentation patterns, rumen microbial protein synthesis, true intestinal digestibility and absorption of nutrients from sunflower-based diets at the small intestines in crossbred dairy cows.